PELATIHAN DAN PENDAMPINGAN PELATIHAN DAN PENDAMPINGAN PENULISAN KARYA TULISAN ILMIAH BAGI GURU SMK NEGERI PURWOSARI BOJONEGORO: PELATIHAN DAN PENDAMPINGAN PENULISAN KARYA TULISAN ILMIAH BAGI GURU SMK NEGERI PURWOSARI BOJONEGORO - Mahmudah, Nur; Kartini, Alif Yuanita (Al-Umron : Jurnal Pengabdian Kepada Masyarakat, 2024)
A scientific paper is a written report containing a presentation of the results of research that has been carried out by a team in accordance with scientific rules and ethics. The ability to write scientific papers for teachers is a professional requirement in career development in teaching and learning. Teachers are required to fulfill the requirements for writing scientific papers in order to be promoted, but this becomes an obstacle due to their low ability and being asked to write in the teacher's environment. Writing scientific papers is an activity related to knowledge and skills in teaching and learning so it is necessary to provide comprehensive, effective and productive training and assistance in writing scientific papers for State Vocational School Teachers in Purwosari. This activity aims to increase the development of teachers' interest in writing in various fields of study. Based on Community Service activities held on 12-13 July 2023 which were attended by 19 teachers consisting of 12 female teachers and 7 male teachers. The results of the PKM activities for Vocational School Teachers in Purwosari can increase knowledge, insight and skills in writing scientific papers and can publish articles independently to meet the professional demands of teaching and learning activities. This activity uses participatory and discussion methods in exploring the writing of scientific papers through training and mentoring in this activity